COMPREHENDING AND CONSUMER ENGAGEMENT IN VIRTUAL BRANDCOMMUNITIES - Makki, Ali (E-Journal VFU, 2025)
Congruity theory is used in this study to examine the dynamics of customer participation in online brand communities (OBCs). It specifically looks at how important aspects that drive customer engagement are self-brand image congruity and value congruity. As a natural byproduct of customer interaction, brand loyalty is also closely examined. The paper provides a conceptual model that shows the connections between various components that are theoretically proposed.